The Pharmaceutical Sciences in 2020: Report of a Conference Organized by the Board of Pharmaceutical Sciences of the International Pharmaceutical Federation (FIP) - Shah, Vinod P. (Springer US, 2010)
The Board of Pharmaceutical Sciences (BPS) of the International Pharmaceutical Federation (FIP) has developed a view on the future of pharmaceutical sciences in 2020. This followed an international conference with invited participants from various fields (academicians, scientists, regulators, industrialists, venture capitalists) who shared their views on the forces that might determine how the pharmaceutical sciences will look in 2020. The commentary here provides a summary of major research activities that will drive drug discovery and development, enabling technologies for pharmaceutical sciences, paradigm shifts in drug discovery, development and regulations, and changes in education to meet the demands of academia, industry and regulatory institutions for pharmaceutical sciences in 2020. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11095-009-0048-3) contains supplementary material, which is available to authorized users.